2021
DOI: 10.1186/s12882-021-02273-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of associations between retinal microvascular parameters and albuminuria in UK Biobank: a cross-sectional case-control study

Abstract: Background Associations between microvascular variation and chronic kidney disease (CKD) have been reported previously. Non-invasive retinal fundus imaging enables evaluation of the microvascular network and may offer insight to systemic risk associated with CKD. Methods Retinal microvascular parameters (fractal dimension [FD] – a measure of the complexity of the vascular network, tortuosity, and retinal arteriolar and venular calibre) were quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Paterson et al . [22] found an independent association between albuminuria and retinal microvascular fractal dimension in fundus photographs. Tom et al .…”
Section: Types Of Systemic Retinal Biomarker Studiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Paterson et al . [22] found an independent association between albuminuria and retinal microvascular fractal dimension in fundus photographs. Tom et al .…”
Section: Types Of Systemic Retinal Biomarker Studiesmentioning
confidence: 83%
“…O'Neill et al [20] found an association between retinal vascular tortuosity and chronic kidney disease (CKD) stages 3-5, while the metaanalysis by Lye et al [21] found no significant association between retinal vascular calibre and CKD, all in fundus photographs. Paterson et al [22] found an independent association between albuminuria and retinal microvascular fractal dimension in fundus photographs. Tom et al [23] and Wang et al [24] found that retinal perfusion and vessel density on OCT-A correlated with CKD in diabetic patients, while Wu et al identified a similar relationship in CKD patients [25].…”
Section: Kidney Disease Biomarkers Identified Without Deep Learningmentioning
confidence: 97%
“…There have been studies exploring the association between retinal FD and renal function based on digital fundus imaging or fundus fluorescein angiography. Some studies indicated a positive association of FD with CKD and GFR (11,28,29), while others showed no Scattergram showing linear correlation between fractal dimension in the superficial capillary plexus and estimated glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function is mostly assessed by flow mediated dilation (FMD) techniques, which require occlusion. Retinal imaging is mostly used to assess the functioning microcirculation, and the macrocirculation function can be assessed by measuring the pulse wave velocity (PWV) as discussed below (67,68).…”
Section: Assessment Of Vascular Functionmentioning
confidence: 99%